A case study from Nigeria - Michael I. Obadan (Intereconomics, 1980)
In INTERECONOMICS No. 4, 1979, Peter Richter suggested that interest payments, royalties and profit retransfers from developing to industrialised countries have already reached such an amazing dimension that the former would in reality have to be regarded as capital exporters rather than importers. The following article supports this proposition with regard to direct investment, using Nigeria as a case study.
Keywords: 330; Direct Foreign Investment